Globalization and labor : democratizing global governance - Stevis, Dimitris; Boswell, Terry (Oxford, 2008)
"Unions have long been a central force in the democratization of national and global governance, and this timely book explores the role of labor in fighting for a more democratic and equitable world. In a clear and compelling narrative, Dimitris Stevis and Terry Boswell explore the past accomplishments and the formidable challenges still facing global union politics. Outlining the contradictions of globalization and global governance, they consider the implications for global union politics since its inception in the nineteenth century. The authors place this key social movement in a political economy framework as they argue that social movements can be fruitfully compared based on their emphases on egalitarianism and internationalism. Applying these concepts to global union politics across time, the authors consider whether global union politics has become more active and more influential or has failed to rise to the challenge of global capitalism. All readers interested in global organizations, governance, and social movements will find this deeply informed work an essential resource."